2022
DOI: 10.1038/s41537-022-00221-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between jumping to conclusions and social cognition in first-episode psychosis

Abstract: Jumping to conclusions (JTC) and impaired social cognition (SC) affect the decoding, processing, and use of social information by people with psychosis. However, the relationship between them had not been deeply explored within psychosis in general, and in first-episode psychosis (FEP) in particular. Our aim was to study the relationship between JTC and SC in a sample with FEP. We conducted a cross-sectional study with 121 patients with FEP, with measures to assess JTC (easy, hard, and salient probability task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…There are This paper is published in BMC Psychiatry You can find it by following this link: https://bit.ly/3Ow5tO7 Please cite the published version several papers discussing the role of JTC in the development of psychosis [e.g., [78][79][80] or schizophrenia [e.g., 81]. Additionally, JTC contributes to impaired emotional recognition and the tendency to make internal attributions for negative events [82]. This implies that clients, guided by an underlying maladaptive belief system, often come to negative conclusions without an attempt to search for a more constructive path.…”
Section: Cognitive Restructuring Aided By Mental Navigationmentioning
confidence: 99%
“…There are This paper is published in BMC Psychiatry You can find it by following this link: https://bit.ly/3Ow5tO7 Please cite the published version several papers discussing the role of JTC in the development of psychosis [e.g., [78][79][80] or schizophrenia [e.g., 81]. Additionally, JTC contributes to impaired emotional recognition and the tendency to make internal attributions for negative events [82]. This implies that clients, guided by an underlying maladaptive belief system, often come to negative conclusions without an attempt to search for a more constructive path.…”
Section: Cognitive Restructuring Aided By Mental Navigationmentioning
confidence: 99%
“…Such cognitive biases are associated with the schizophrenia spectrum [ 49 , 50 ] and often manifest as jumping to conclusions (making judgments without a sufficient amount of information) and belief inflexibility, external attribution bias, or paying attention to threats (excessive perception of others’ behavior as threatening) [ 51 ]. They could be also social cognition problems [ 52 ]…”
Section: Introductionmentioning
confidence: 99%
“…Such cognitive biases are associated with the schizophrenia spectrum [49,50] and often manifest as jumping to conclusions (making judgments without a sufficient amount of information) and belief inflexibility, external attribution bias, or paying attention to threats (excessive perception of others' behavior as threatening) [51]. They could be also social cognition problems [52] Many studies have confirmed that exaggerated cognitive biases are observed along the continuum of psychosis from psychotic-like experiences (PLEs) to full-blown psychosis [50]. In addition, besides being one of the characteristics of psychosis, cognitive biases play an important role in the appearance of psychotic symptoms, e.g., hallucinations and delusions-even among healthy individuals [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…MCT includes sessions that work on domains of social cognition such as facial emotion recognition and theory of mind, both of which are strong predictors of outcome [ 12 ]. Likewise, it targets the jumping-to-conclusions bias (JTC), which has been repeatedly associated with delusions, poorer neurocognition, and measures of outcome [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%